Analisis Hukum Ekonomi Syariah terhadap Praktik Pinjaman Online: Tinjauan Unsur Riba,Gharar dan Tadlis pada Aplikasi Adapundi di Dusun Kebonan Kecamatan Gumukmas - Firdatul Halimah; Muhammad Hamdi (Jurnal Riset Ekonomi dan Akuntansi, 2026)
This study aims to evaluate the practices of online lending on the Adapundi platform in Kebonan Village, Gumukmas District, through a Sharia Economic Law review focusing on the elements of Riba (usury), Gharar (uncertainty), and Tadlis (deception). Utilizing a qualitative field research method with a normative-empirical approach, data were gathered through observations of application functionality and in-depth interviews with debtors to dissect contract structures and information transparency. The findings reveal a significant discrepancy between digital representation and the reality of fund disbursement, where customers often receive funds that have been deducted upfront (discounting) yet remain burdened with the obligation to repay the full initial nominal amount. This practice is identified as containing elements of Gharar fil Miqdar due to the lack of clarity regarding the actual nominal received , Riba Qardh in the deduction of fees that lack a fair compensation basis ('iwadh) , and indications of Tadlis through misleading visual strategies within the application. These findings emphasize that such transaction mechanisms violate the principle of absolute consent (An-Taradin) and create structural imbalances or injustice (Dzulm) that harm the community. This study recommends the need for strengthening public literacy and transforming fintech service systems to align with the values of Islamic economic justice.